2021
DOI: 10.1111/jgh.15493
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual blood‐derived mesenchymal stem cells attenuate inflammation and improve the mortality of acute liver failure combining with A2AR agonist in mice

Abstract: Background and Aim Acute liver failure (ALF) poses a serious public health issue. The menstrual blood‐derived mesenchymal stem cells (MenSCs) have been applied to cure various liver‐related diseases. However, the efficacy and mechanism are far from clear. This study aims to explore the efficacy and potential mechanism of MenSCs to cure ALF. Methods We investigate the potential mechanism of MenSCs on the ALF in vitro and in vivo. A2A adenosine receptor (A2AR) activation was investigated as the potential reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Meanwhile, adenosine A2A receptor (A2AR) agonists can synergize with the menstrual blood MSCs. 72 Sang et al 73 found that MSCs transplantation combined with IL-1Ra (2 mg/kg) can significantly improve the survival time of ALF swine, which may be related to the synergistic effect of MSCs and IL-1Ra in regulating inflammation and apoptosis. In ALF rat , Human umbilical cord blood MSCs transplantation combined granulocyte colony stimulating factor can reduce liver injury by inhibiting inflammation, oxidative stress, and hepatocyte apoptosis and promoting the proliferation and colonization of MSCs.…”
Section: Combination Therapy Of Mscsmentioning
confidence: 99%
“…Meanwhile, adenosine A2A receptor (A2AR) agonists can synergize with the menstrual blood MSCs. 72 Sang et al 73 found that MSCs transplantation combined with IL-1Ra (2 mg/kg) can significantly improve the survival time of ALF swine, which may be related to the synergistic effect of MSCs and IL-1Ra in regulating inflammation and apoptosis. In ALF rat , Human umbilical cord blood MSCs transplantation combined granulocyte colony stimulating factor can reduce liver injury by inhibiting inflammation, oxidative stress, and hepatocyte apoptosis and promoting the proliferation and colonization of MSCs.…”
Section: Combination Therapy Of Mscsmentioning
confidence: 99%
“…In addition, in vitro studies demonstrated that MenSCs had a negative effect on macrophage bactericidal properties and the production of reactive oxygen intermediates, indicating that MenSCs effect the macrophage numbers, which provides a theoretical basis for clinical treatment in future ( 32 ). Moreover, MenSCs can have a negative effect on PI3K/Akt/mTOR/IKK signaling mediated by TLR4, leading to a decreasing of inflammatory cytokine, as p-NF-κBp65 could not be translocated into the nucleus ( 33 ). Another study showed that the maturation of human blood monocyte-derived dendritic cells was suppressed via interleukin−6 and interleukin−10(IL-10) secreted by MenSCs ( 34 ).…”
Section: The Immunomodulatory and Anti-inflammatory Function Of Menscsmentioning
confidence: 99%
“…Human menstrual blood–derived endometrial stem cells (MenSCs), an important member of the MSC family, have attracted extensive attention because of their rich sources, noninvasive collection and separation methods, high proliferative activity, and differentiation potential 22 . MenSCs have satisfactory results in the treatment of osteogenesis, cardiac, liver, lung, endometrial, stroke, and other diseases 22 27 . Owing to their excellent biological characteristics, MenSCs have received extensive attention as seed cells for the treatment of refractory diseases.…”
Section: Introductionmentioning
confidence: 99%